2007
DOI: 10.1111/j.1445-2197.2007.04293.x
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Grafting of the Thoracic Aorta, an Evolving Therapy: Ten‐year Experience in a Single Centre

Abstract: Endovascular grafting of the thoracic aorta is an evolution in the treatment of thoracic aortic pathology. The results of elective endovascular grafts were acceptable. Emergency procedures had a higher incidence of complications and death. Improvement in graft technology, design and deployment are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 38 publications
0
12
1
3
Order By: Relevance
“…9,11,12,18,24,25,[36][37][38][39][42][43][44] Fig 3). 6,9,11,12,[14][15][16][17][18][19][20][21][22][23][24][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][45][46][47][48] Again, there was no evidence of heterogeneity (Cochran Q, 10.74; P ϭ .99) or bias (Egger 0.10; P ϭ .50). However, no significant difference was noted in the risk of SCI with LSA coverage and preoperative revascularization compared with no LSA coverage (0.8% vs 2.7%, respectively; POR, 1.69; 95% CI, 0.56-5.15; P ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,11,12,18,24,25,[36][37][38][39][42][43][44] Fig 3). 6,9,11,12,[14][15][16][17][18][19][20][21][22][23][24][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][45][46][47][48] Again, there was no evidence of heterogeneity (Cochran Q, 10.74; P ϭ .99) or bias (Egger 0.10; P ϭ .50). However, no significant difference was noted in the risk of SCI with LSA coverage and preoperative revascularization compared with no LSA coverage (0.8% vs 2.7%, respectively; POR, 1.69; 95% CI, 0.56-5.15; P ...…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, some series have shown a correlation between concomitant or previous abdominal aortic aneurysm repair and SCI. 11,33 This finding is not universal, however. 37,49 Lastly, the contribution of cerebrospinal fluid drainage is also unclear from the data.…”
Section: Figmentioning
confidence: 90%
“…Cheung et al 9 showed a risk of SCI after TEVAR of 11.8% in patients with prior AAA repair (2 of 17) and 5.2% in patients without prior AAA repair (3 of 58). Sandroussi et al 14 showed that paraplegia was significantly associated with previous AAA repair in a group of patients that underwent TEVAR for aortic dissections, aneurysms, traumatic ruptures, penetrating ulcers, or other indications (relative risk [RR] 7.125, P .02). Chiesa et al 8 described also a group of patients that underwent TEVAR for aneurysm, dissection, or ulcer and reported that patients with previous or concomitant AAA repair had an increased risk of neurological deficit (P .08).…”
mentioning
confidence: 99%
“…Australasia's vascular surgeons continue to push the boundaries of endovascular aortic repair for ever more complex disease, particularly of the thoracic and thoracoabdominal aorta, and for infrarenal aortic disease with complex iliac anatomy. [20][21][22][23][24] Australasia's surgeons are participating in device trials for acute thoracic aortic dissection, 25 and funding is being sought to establish a registry to monitor the outcomes of TEVAR for traumatic thoracic aortic tear. A number of groups have active research programs examining the prevalence, biology, and genetics of aortic and peripheral arterial diseases in an effort to define roles for screening and possible medical interventions.…”
Section: Research Challenges For Vascular Surgery In Australasiamentioning
confidence: 99%